2009
DOI: 10.4088/jcp.08m04545
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-Up of Syndromal Antisocial Behavior in Adults

Abstract: Objective-To present nationally representative findings on total antisocial personality disorder (ASPD) symptoms, major violations of others' rights (MVOR), and violent symptoms over a 3-year follow-up in Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions among adults diagnosed at Wave 1 with ASPD versus syndromal adult antisocial behavior without conduct disorder before age 15 (AABS, not a codable DSM-IV disorder).Method-Face-to-face interviews were conducted with 34,653 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 125 publications
(101 reference statements)
1
15
0
Order By: Relevance
“…Fourth, participants may have underreported anger, due to concerns of social desirability. However, previous studies with the NESARC have reported even higher rates of other socially undesirable attributes such as shoplifting 60 or firesetting, 61 domestic violence, and commission of illegal acts 62-64 suggesting that underreporting of anger, if present, is unlikely to be substantial. Despite these limitations, the NESARC provides detailed nationally representative survey data on anger and its correlates.…”
Section: Discussionmentioning
confidence: 86%
“…Fourth, participants may have underreported anger, due to concerns of social desirability. However, previous studies with the NESARC have reported even higher rates of other socially undesirable attributes such as shoplifting 60 or firesetting, 61 domestic violence, and commission of illegal acts 62-64 suggesting that underreporting of anger, if present, is unlikely to be substantial. Despite these limitations, the NESARC provides detailed nationally representative survey data on anger and its correlates.…”
Section: Discussionmentioning
confidence: 86%
“…Those assessed at Wave 1 included avoidant, dependent, obsessive-compulsive, paranoid, schizoid, and histrionic PDs (Grant et al, 2004c). Antisocial PD was assessed at Wave 1 with a follow-up at Wave 2 to capture individuals who may not have met full diagnostic criteria at Wave 1 but went on subsequently to do so (Goldstein and Grant, 2009). Borderline, narcissistic, and schizotypal PDs were assessed at Wave 2 (Grant et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In older adults, persistent mood and anxiety disorders were predicted by physical and mental comorbidity [224]. Persistent antisocial symptoms were predicted by being unmarried, low SES, and comorbidity [285]. Relapse.…”
Section: Major Findingsmentioning
confidence: 99%